A comprehensive prospective examination of purposeful heading in American interscholastic and collegiate soccer players. Issue 2 (2nd April 2020) - Kaminski, Thomas W.; Weinstein, Sarah; Wahlquist, Victoria E.
ABSTRACT: Purpose: The popularity of soccer worldwide is unquestionable, yet the aspect of purposeful heading in the sport has drawn increasing scrutiny over the past 10 years. The reason for this is primarily be-cause of the concern over the potential deleterious effects of repetitive head impacts (RHI) on brain structure and function. Accurate accounts of the header burden in soccer are needed to determine how frequently the activity occurs during practice and competition. Utilizing robust prospective database, this report provides a significant look into soccer heading exposure in both interscholastic (10 yr.-matches) and collegiate (15 yr.-practices & matches) cohorts in the United States. Methods: Headers/game exposure rates were 1.68 (interscholastic girls), 2.36 (collegiate women), and 3.55 (collegiate men). Results: Overall, the data suggests that in our cohorts of soccer players, the exposure to soccer heading in both practice and game settings is relatively low. Conclusions: Our soccer heading tabulation system accounted for 4 types of headers including clear, pass, shot, and unintentional deflection. Fortunately, the "unintentional deflections" (blows to the head) accounted for an extremely low number (range 2-5%) of the total soccer heading exposures. Additional research is needed to best understand the implications of these small number of RHI on long-term brain function and behavior.